Sinus and venous thrombosis - A differential diagnosis of acute stroke - Grunwald, I; Politi, M; Holst, B; Dorenbeck, U; Papanagiotou, P; Reith, W (2005)
Thrombosis of the cerebral veins and sinus is a rare, but important cause of stroke. The clinical picture varies. This contribution addresses the etiology, clinical picture, imaging procedures, and therapeutic options. © Springer Medizin Verlag 2005.